Introduction of STEAM for Preparing Innovative Elementary Teachers in Science - Rizki Putri Wardani; Chumi Zahroul Fitriyah (International Conference on Elementary Education, 2023)
21st-century competence was always been a concern in this era. It was very important to full fill student and teacher competence. It is called 4Cs, namely creative thinking skills, critical thinking skills, communication skills, and collaborative skills. There was one of the learning that in accordance with the 21st century, was STEAM (Science, Technology, Engineering, Arts, and Mathematics). Before preparing students to gain this competence to introduce STEAM, it is important to needed preparing for innovative teachers soon in university or lecturers about STEAM. One of the lecturers in PGSD was called Learning Plan in Elementary or “Perencanaan Pembelajaran SD” which introduced STEAM in science and its implementation of it. The objective of this research was to know the capability of college students to prepare and practice STEAM in science matters. It used the descriptive quantitative method by the percentage of identifying implantation STEAM in science matter. 35 College student of PGSD as a subject of this research was taking Learning Plan as Elementary lecturer. The result shows that about 80% of college students have been planning STEAM as evidenced by designing STEAM and practicing teaching aids. It can be concluded that introducing STEAM for a college student can be applied to innovative teachers soon.